1987
DOI: 10.1063/1.338024
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation-mechanics-based constitutive relations for material dynamics calculations

Abstract: An improved description of copper- and iron-cylinder impact (Taylor) test results has been obtained through the use of dislocation-mechanics-based constitutive relations in the Lagrangian material dynamics computer program EPIC-2. The effects of strain hardening, strain-rate hardening, and thermal softening based on thermal activation analysis have been incorporated into a reasonably accurate constitutive relation for copper. The relation has a relatively simple expression and should be applicable to a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
693
2
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,699 publications
(796 citation statements)
references
References 17 publications
13
693
2
12
Order By: Relevance
“…We therefore evaluate a number of models which are best suited to the regime of interest to us. This regime consists of strain-rates between 10 3 /s and 10 6 /s and temperatures between 230 K and 800 K. We have observed that the combined effect of high temperature and high strain-rates has been glossed over in most other similar works (for example Zerilli and Armstrong (1987); Johnson and Holmquist (1988); Zocher et al (2000)). Hence we examine the temperature dependence of plastic deformation at high strain-rates in some detail in this paper.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…We therefore evaluate a number of models which are best suited to the regime of interest to us. This regime consists of strain-rates between 10 3 /s and 10 6 /s and temperatures between 230 K and 800 K. We have observed that the combined effect of high temperature and high strain-rates has been glossed over in most other similar works (for example Zerilli and Armstrong (1987); Johnson and Holmquist (1988); Zocher et al (2000)). Hence we examine the temperature dependence of plastic deformation at high strain-rates in some detail in this paper.…”
Section: Introductionmentioning
confidence: 54%
“…These models are the Johnson-Cook model (Johnson and Cook (1983)), the Steinberg-Cochran-Guinan-Lund model (Steinberg et al (1980); Steinberg and Lund (1989)), the Zerilli-Armstrong model (Zerilli and Armstrong (1987)), the Mechanical Threshold Stress model (Follansbee and Kocks (1988)), and the Preston-Tonks-Wallace model (Preston et al (2003)). We also evaluate the associated shear modulus models of Varshni (1970), Steinberg et al (1980), and Nadal and Le Poac (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Those proposed by Cowper and Symonds [5] and Johnson and Cook [6] are empirical, and in that due to Zhao [7], an extension of the Tanimura formulation [47], temperature effects are not included. Zerilli and Armstrong [9] proposed a constitutive relation coupled with temperature and with some background of materials science. Next, a comparison between some of these constitutive relations for sheet steel ES is performed, Fig.…”
Section: Thermoviscoplastic Modelingmentioning
confidence: 99%
“…Based on the intrinsic characteristics of dislocation and microstructure, Zerilli and Armstrong [30] made the athermal stress to Hall-Petch relationship for FCC metal. Jiang et al [24] developed the Hall-Petch relationship associated with the dislocation pile-up theory and flow stress-grain size relationship as:…”
Section: Constitutive Modellingmentioning
confidence: 99%